Three isoforms of exosomal circPTGR1 promote hepatocellular carcinoma metastasis via the miR449a–MET pathway - Wang, Guoying; Liu, Wei; Zou, Yong; Wang, Genshu; Deng, Yinan; Luo, Jingyan; Zhang, Yingcai; Li, Hua; Zhang, Qi; Yang, Yang; Chen, Guihua (EBioMedicine, 2019)
The role of exosomal circular RNAs (circRNAs) in Hepatocellular carcinoma (HCC) cells with high metastatic potential has been little studied. Exosomal circRNA from cells with non-metastatic (HepG2), low metastatic (97L), and high metastatic (LM3) potential were sequencing. Metastatic-related circRNAs in serum from HCC patients were measured and their association with clinical prognosis was evaluated. Furthermore, candidate functional circRNAs in LM3-derived exosomes was assessed. LM3 exosomes enhanced the cell migration and invasion potential of HepG2 and 97 L cells. CircPTGR1, a circRNA with three isoforms, was specifically expressed in exosomes from 97 L and LM3 cells, upregulated in serum exosomes from HCC patients and was associated with the clinical stage and prognosis. Knockdown of circPTGR1 expression suppressed the migration and invasion of HepG2 and 97L cells induced by co-culturing with LM3 exosomes. Bioinformatics, co-expression analysis, and a luciferase assay indicated that circPTGR1 competed with MET to target miR449a. Higher metastatic HCC cells can confer this potential on those with lower or no metastatic potential via exosomes with circPTGR1, resulting in increased migratory and invasive abilities in those cells. National Natural Science Foundation of China (No. 81470870, 81670601, 81570593), Guangdong Natural Science Foundation (No. 2015A030312013, 2015A030313038), Sci-tech Research Development Program of Guangdong Province (2014B020228003), Sci-tech Research Development Program of Guangzhou City (No. 201508020262, 201400000001-3, 201604020001, 201607010024), Innovative Funds for Small and Medium-Sized Enterprises of Guangdong Province (2016A010119103), Pearl River S&T Nova Program of Guangzhou (201710010178), and National 13th Five-Year Science and Technology Plan Major Projects of China (No. 2017ZX10203205-006-001).